FRI0237 Widespread Pain is Common in Patients with Axial Spondyloarthritis: A Topographical Analysis of Body Charts and the Relationship With Clinical Variables. (9th June 2015) - Swinnen, T.; Raddoux, E.; Van Rietvelde, T.; Dankaerts, W.; Westhovens, R.; de Vlam, K.
Abstract : Background: Pain is a core outcome domain in the assessment of axial spondyloarthritis (aSpA) and can be therapeutically challenging. To date, only (spinal) pain intensity is captured in this patient group via numerical rating scales. State-of-the-art physiological insights suggest a role for topographical analysis to classify underlying pain mechanisms in clinical practice 1 . Unfortunately, no data on "the spread of pain" are available in aSpA. Objectives: To explore pain locations and widespread pain in patients with aSpA and to explore their relationship with clinical variables. Methods: We collected demographics, the Bath Ankylosing Spondylitis Functional Index (BASFI), the Bath Ankylosing Spondylitis Disease Activity Index total score (BASDAItot), stiffness items combined (BASDAIstiff) and spinal pain item (BASDAIpain) and the Bath Ankylosing Spondylitis Metrology Index (BASMI) in 125 participants with aSpA (male/female: 80/45; mean ± SD, age: 43.9±11.67 yrs; height: 171.06±9.54cm; weight: 76.96±15.27;BASMI: 3.27±1.78;BASFI: 3.81±2.57;BASDAI: 3.88±2.26; Biologicals yes/no: 65/60; disease duration: 13.23±9.99). Body charts divided in 80 body regions (20 spinal) were filled in by patients and informed on pain locations during the last week. Body charts were scored using a grid by two independent raters (mean kappa 0.940, range 0.778-1.00). Spearman rank correlations were used to examine relationships with clinical variables (p<0.05). Results: Low back pain was reported by 94 patients (75%), while only low back (22;18%), thoracic (2; 2%) and cervical (3; 2%) pain was remarkably rare. Similarly, leg pain was infrequent (right: 3; 2.4%, left: 1; 0.8%). Widespread pain in all spinal regions was common (49, 40%). Low back pain correlated with thoracic (R=0.377; P<0.01) and cervical pain (R=0.180; P<0.05). The sum of the all painful regions was associated with BASDAItot (R=0.547; P<0.01), BASDAIpain (R=0.477; P<0.01), BASDAIstiff (R=0.413; P<0.01) and BASFI (R=0.405; P<0.01), indicating that the spread of pain is a related but distinct clinical construct. BASMI was not related to body chart outcomes (p>0.05). Conclusions: Widespread spinal is a common clinical feature in aSpA that is associated with disease-specific outcome measures. Body charts add essential information in the assessment of pain and are a valuable focus for future research in aSpA. References: Malfait AM, Schnitzer TJ. Towards a mechanism-based approach to pain management in osteoarthritis. Nat Rev Rheumatol. 2013 Nov;9(11):654-64. Disclosure of Interest: None declared